Do Multilingual Speakers Understand the Bible Best in Their Heart Language? A Tool for Comparing Comprehension of Translations in Vernacular Languages and Languages of Wider Communication. Issue 1 (April 2014) - Nehrbass, Kenneth
It has been argued that speakers who are fluent in a vernacular and language of wider communication (LWC) will inevitably understand the Scriptures better in their "heart language." I designed an experiment to determine the validity of that argument, using comprehension checks of seven passages in the New Testament that are difficult to comprehend. Preliminary results suggest that bilingual speakers performed better during checking sessions conducted in the LWC than they did while using the receptor language (RL), but their ability to identify key themes in either language was equivalent. While the experiment calls into question the validity of the "heart-language argument, " I conclude that there are several other more compelling reasons for producing vernacular Bible translations.